eCM 2023
DOI: 10.22203/ecm.v045a03
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial cyclic stretch enhances osteogenic differentiation of OPLL-derived primary cells via YAP-Wnt/β-catenin axis

et al.

Abstract: The pathogenesis of posterior longitudinal ligament ossification (OPLL) remains inadequately understood. Mechanical stimulation is one of the important pathogenic factors in OPLL. As one of the mechanical stimulation transduction signals, the yes-associated protein (YAP) interacts with the Wnt/β-catenin signalling pathway, which plays an important role in osteogenic differentiation. This study aimed to demonstrate the role of YAP-Wnt/β-catenin axis in cell differentiation induced by mechanical stress. Primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The PLL located in the intervertebral space is subjected to tensile stress due to the spine’s flexion and extension, while the PLL close to the vertebral body is subjected to less tensile stress due to its close connection to the vertebral body. Furthermore, immunofluorescence staining indicated a significant increase in YAP expression at the site of ligamentous heterotopic ossification, which is consistent with previous in vitro studies ( Zhu et al, 2023 ). This finding suggests that mechanical stimulation plays a vital role in the pathological process.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The PLL located in the intervertebral space is subjected to tensile stress due to the spine’s flexion and extension, while the PLL close to the vertebral body is subjected to less tensile stress due to its close connection to the vertebral body. Furthermore, immunofluorescence staining indicated a significant increase in YAP expression at the site of ligamentous heterotopic ossification, which is consistent with previous in vitro studies ( Zhu et al, 2023 ). This finding suggests that mechanical stimulation plays a vital role in the pathological process.…”
Section: Discussionsupporting
confidence: 91%
“…They allow researchers to study the pathophysiological mechanisms of diseases and potential treatments more accurately. Previous research has shown that mechanical stimulation has a significant impact on cell osteoblastic differentiation at the cellular level, and this process is associated with the nuclear translocation of the mechanical signal response factor YAP ( Zhu et al, 2023 ). In this study, we aimed to establish an appropriate animal model that can serve as a basis for further in vivo investigation of this mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, under dynamic culture conditions, primary cells from patients with heterotopic ossification showed significantly raised expression of osteogenic marker genes compared to static culture, indicating that mechanical stimulation may promote osteogenic differentiation of ligaments [58]. Zhu et al found that mechanical stimulation had a significant effect on osteoblast differentiation at cellular level, which was related to the nuclear translocation of the mechanical signaling response factor YAP [59]. On this basis, they used CRISPR/Cas9 technology to establish EIIa cre -Enpp1 flox/flox genedeficient mice and demonstrated that mechanical stimulation played a key role in the pathological process of heterotopic ossification of tendons and ligaments.…”
Section: The Impact Of Physical Therapy On Disease Via Hippo/ Yap Sig...mentioning
confidence: 99%